Kesalahan Berbahasa pada Teks Anekdot Politik Lucu pada Website https://edukasi.okezone.com Edisi Januari 2025 - Haris Budisetiawan; Ezra Malvino Putra Alwi; Azi Aurahman Elegan; Muhammad Rolanda Hendrakusuma; Arshi Vinusia; Marta Alfiana Damayanti; Riri Kumala Sari; Samuel B.T. Simorangkir (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2025)
Language assumes a fundamental role in human life and is essential for communication and survival. This research aims to explore and analyze the various types of phrases that are found in the online article entitled "Funny Anecdote Political Texts" published on the laman web https://edukasi.okezone.com. The objective is to understand how phrases are used and to identify the phrase structures that appear within the selected anecdotal texts. This study is considered important because it contributes to the field of syntax in linguistic studies and offers insights into the phrase patterns commonly employed in humorous political anecdotes. Data were collected through library research using observation and note-taking techniques, with the researchers acting as observers and language analysts throughout the process. A phrase is defined as a group of words that function as a single unit but do not convey a complete idea. Since a phrase does not express a full thought, it requires additional elements to form a clause or complete sentence. This study helps readers gain a clearer understanding of phrase structures and their functions within political anecdotal discourse.